Pemanfaatan Aplikasi Food Chain Dalam Pembelajaran IPA untuk SMP Kelas 7 - Septia Winariani, Pradnya; Wardana, Rizky Amelia; Sabilatuzzahra, Putri Alifiyah; Subekti, Hasan; Hidayati, Siti Nurul; Vika Aulia, Ernita (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
Science education in junior high schools plays an important role in shaping students’ critical and systematic thinking. However, abstract topics such as food chains often pose challenges for students and require appropriate learning media. This study aims to examine the use of the Food Chain application as an interactive learning tool to improve students’ understanding and motivation in learning food chain concepts. The research employed a qualitative method through literature review, focusing on interactive media and contextual learning in science education. Results indicate that the Food Chain application enables students to visualize trophic levels, understand ecological relationships, and engage actively in the learning process. The application supports critical thinking and problem-solving skills by offering simulation-based exploration. Moreover, it enhances students’ motivation by presenting dynamic, visual, and interactive content. The integration of this technology also allows teachers to monitor student progress in real-time and adjust learning strategies accordingly. Therefore, the Food Chain application is a promising innovation in science learning that aligns with 21st-century education demands and the goals of sustainable development.